Fold modulating function: bacterial toxins to functional amyloids - Syed, Adnan K.; Boles, Blaise R. (Frontiers in Microbiology, 2014)
Many bacteria produce cytolytic toxins that target host cells or other competing microbes. It is well known that environmental factors control toxin expression, however recent work suggests that some bacteria manipulate the fold of these protein toxins to control their function. The β-sheet rich amyloid fold is a highly stable ordered aggregate that many toxins form in response to specific environmental conditions. When in the amyloid state, toxins become inert, losing the cytolytic activity they display in the soluble form. Emerging evidence suggest that some amyloids function as toxin storage systems until they are again needed, while other bacteria utilize amyloids as a structural matrix component of biofilms. This amyloid matrix component facilitates resistance to biofilm disruptive challenges. The bacterial amyloids discussed in this review reveal an elegant system where changes in protein fold and solubility dictate the function of proteins in response to the environment.